Effects of Ferrule and Diameter of Parallel Cast Post and Core on Fracture Resistance - Maalhagh-Fard, Ahmad; Pacheco, Rafael Rocha; Gill, Karanjot; Wagner, Warren Charles (Brazilian Dental Science, 2019)
Objectives: The aim of this study was to evaluate the effects of using different diameters of parallel cast posts with, or without ferrule, on the overall fracture resistance of Cast Post and Core (CPC).Material and methods: Forty (40) endodontically treated human maxillary central incisors were divided into four groups (n=10): [F1] 1.0 mm diameter post with ferrule; [NF1] 1.0 mm diameter cast post without ferrule; [F1.5] 1.5 mm diameter cast post with ferrule; [NF1.5] 1.5 mm diameter post without ferrule. For all teeth, the post space (9.0 mm, in depth) was prepared using ParaPostTM drill. CPC using base metal alloy were fabricated and were cemented using resin modified glass ionomer (RMGI) cement along with the PFM crowns. A universal testing machine (Instron) was used to apply horizontal force perpendicular to the long axis of the tooth at the center of lingual surface, until catastrophic failure. Data was submitted to two-way ANOVA and Scheffé tests (P